O ENSINO SECUNDÁRIO EM CAMPO GRANDE (1930-1961): RELAÇÃO PÚBLICO E PRIVADO - Paolla Rolon Rocha (2023)
The thesis is linked to the History, Policies and Education Research Line of the Postgraduate Program in Education at the Federal University of Mato Grosso do Sul and is part of the research entitled "Por uma outra Historiografia do Ensino Secundário (1931-1961): Comparative Studies as Construction Tools", coordinated by Prof. Dr. Fabiany de Cássia Tavares Silva, as well as Prof. Dr. Margarita Victoria Rodríguez's project under the title "Political and pedagogical proposals for the education of liberal and critical organic intellectuals in Brazil (1920-2000)". The aim is to understand the relationship between public and private secondary education in terms of its expansion, as well as the tensions and interests that existed in promoting private secondary education between 1930 and 1961 in the municipality of Campo Grande. The methodological procedures of the research consisted of the collection and documentary analysis of legal norms at national, state and municipal level that regulated secondary education, as well as population statistics and financial balances, in addition to scientific publications such as books, theses and dissertations on secondary education in Campo Grande. The categories of analysis are: public-private relationship; educational policy and the state; the categories of method: contradiction; universal and singular. The results show that, between 1920 and 1961, the following private secondary education institutions were set up in the city of Campo Grande: Intituto Pestalozzi (1917), which later became Colégio Dom Bosco (1930), Colégio Nossa Senhora Auxiliadora (1926), Instituto Osvaldo Cruz (1927) and Ginásio Barão do Rio Branco (1949), as well as the public schools Liceu Campo-Grandense (1939) and Escola Normal Joaquim Murtinho (1931). Throughout the period studied, it became clear that, at national and state level, the state had no effective commitment to promoting secondary education, since there was no demand for it. In the city of Campo Grande, private initiative contributed to the start of this stage of education. It was also observed that this situation was opportune for the government, as it removed its responsibility and commitment to the materialization of secondary education. In this way, the participation of the private sector was encouraged, especially confessional institutions, in exchange for scholarships granted to students from working class backgrounds. As a result, over the years, the state has contributed to perpetuating the social differences that stem from capitalist society. Keywords: secondary education; public and private; history of education; Campo Grande.